A stubborn persistence: Is the stability of leverage ratios determined by the stability of the economy? - Hanousek, Jan; Shamshur, Anastasiya (Journal of Corporate Finance, 2011)
The choice of capital structure firms make is a fundamental issue in the financial literature. According to a recent finding, the capital structure of firms remains almost unchanged during their lives. This stability of leverage ratios is mainly generated by an unobserved firm-specific effect that is liable for the majority of the variation in capital structure. We demonstrate that even substantial changes in the economic environment do not affect the stability of firms' leverage due to the presence of credit constraints. Financially unconstrained firms are more responsive to economic changes and adjust to the target substantially faster than constrained firms. Moreover, accounting for the ownership structure of firms boosts the explanatory power of the model in the subsample of unconstrained firms, suggesting that annual information on ownership and ownership changes together with financial constraints have the potential to be an answer to the puzzle of stability in capital structure.